The shift culture in engineering education : Are we ready? / Asmidar Alias and Norshariza Mohamad Bhkari - Alias, Asmidar; Mohamad Bhkari, Norshariza (Universiti Teknologi MARA Cawangan Pahang, 2008)
The culture in engineering education needs to be shifted from the conventional method to a more effective one. Graduates cannot fulfill requirements from industry because they lack of soft skills and this is one of the unemployment issues in Malaysia recently. A shift culture is, therefore, needed to improve curriculum in higher learning institutions. Thus, the Outcome-Based Education (OBE) is introduced in engineering programmes as an initiative pilot study solicited by Ministry of Higher Education (MOHE). This paper discusses the need of change affected by the programme accreditation, needs from the industry and Continual Quality Improvement (CQI). The paper also focuses on the programme administration. Several actions have been taken by the Faculty of Civil Engineering (FCE), UiTM towards the implementation of OBE. These include the awareness of the changes from all engineering education parties, the sharing of UiTM experiences, and the practice on developing skills and standardisation. A few recommendations have been proposed such as the need of experts, details for student qualification and the need of regular discussions among lecturers to enable the transition of culture shift embraced in harmony.